2022
DOI: 10.3389/fimmu.2022.926262
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid Specific Diagnostics for the Detection of Divergent SARS-CoV-2 Variants

Abstract: Since the start of the COVID-19 pandemic, multiple waves of SARS-CoV-2 variants have emerged. Of particular concern is the omicron variant, which harbors 28 mutations in the spike glycoprotein receptor binding and N-terminal domains relative to the ancestral strain. The high mutability of SARS-CoV-2 therefore poses significant hurdles for development of universal assays that rely on spike-specific immune detection. To address this, more conserved viral antigens need to be targeted. In this work, we comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Six-week-old female mice carrying the human ACE2 gene under the control of the keratin 18 promoter (K18-hACE2) on C57BL/6J background were purchased from Animal Resource Centre (ARC) in Australia and randomly assigned to cages. Group sizes were determined based on our previous studies [ 4 , 29 ], and contained n = 6 for clinical scoring and n = 4 for tissue collection. Mice were anesthetized with ketamine (100 mg/kg) and xylazine (10 mg/kg), followed by intranasal inoculation of 20 µL of the ancestral SARS-CoV-2 (Wu strain) at 5 x 10 3 FFU per mouse, or RPMI additive free medium for the uninfected control group.…”
Section: Methodsmentioning
confidence: 99%
“…Six-week-old female mice carrying the human ACE2 gene under the control of the keratin 18 promoter (K18-hACE2) on C57BL/6J background were purchased from Animal Resource Centre (ARC) in Australia and randomly assigned to cages. Group sizes were determined based on our previous studies [ 4 , 29 ], and contained n = 6 for clinical scoring and n = 4 for tissue collection. Mice were anesthetized with ketamine (100 mg/kg) and xylazine (10 mg/kg), followed by intranasal inoculation of 20 µL of the ancestral SARS-CoV-2 (Wu strain) at 5 x 10 3 FFU per mouse, or RPMI additive free medium for the uninfected control group.…”
Section: Methodsmentioning
confidence: 99%
“…These test systems allowed detection of as low as 8 pg of a purified protein or 625 TCID 50 /mL of a virus, and they cross-reacted with the P.1 and B.1.617.2 variants [ 52 ]. The use of N-specific detection by highly sensitive nanobodies C2 and E2, which are specific to B.1, P.1 and B.1.617.2, was demonstrated by Isaacs et al [ 53 ]. Molecular modeling of the interaction of anti-N mAbs specific to 501Y.V1-V3, obtained by Yamaoka et al [ 54 ], revealed binding with exterior protein surface epitopes, and immunochromatographic test systems, combined with silver amplification technology, were developed.…”
Section: Discussionmentioning
confidence: 99%
“…019-19741); anti-SARS-CoV-2 Nucleocapsid C2, 1:1,000 (ref. 62 ); anti-SARS-CoV-2 Spike protein, 1:1,000 (ref. 63 ); anti-γH2AX (Millipore, 1:1,000, no.…”
Section: Methodsmentioning
confidence: 99%